Dialogue training as a condition of humanization of pedagogical activity - Максименко, І. Г. (Pedagogy of Higher and Secondary Education, 2012)
Maksymenko I. H. Dialogue learning as a condition of humanization of pedagogical activity. The article deals with the organization of dialogue training as a condition of humanization of educational activities.